Method for manufacturing solid-state battery

By controlling the pressing pressure and adhesive content, the manufacturing method of the solid battery was improved, the bonding problem between the solid electrolyte layer and the positive electrode layer was solved, and the stability of the battery performance and the improvement of the capacity were achieved.

CN120728015APending Publication Date: 2025-09-30HONDA MOTOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510233081.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-30
Filing Date
2025-02-28
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

In the prior art, the interface contact between the solid electrolyte layer and the positive and negative electrode layers is easily deteriorated, resulting in a voltage drop. Moreover, when a thick positive electrode active material layer is formed, the positive electrode active material layer is easily extended, affecting the bonding property.

Method used

A stacking process is adopted, including a transfer pressing process, a first pressurizing process and a second pressurizing process. By controlling the pressing pressure and the adhesive content, the bonding between the solid electrolyte layer and the positive electrode layer is improved. Specific measures include that the pressing pressure in the transfer pressing process is less than that in the first pressurizing process, the adhesive content of the first solid electrolyte layer is higher than that of the second solid electrolyte layer, and the thickness of the first solid electrolyte layer is thinner than that of the second solid electrolyte layer.

Benefits of technology

The bonding between the solid electrolyte layer and the positive electrode layer is improved, ensuring the battery performance stability and capacity and avoiding voltage drop.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120728015A_ABST
    Figure CN120728015A_ABST
Patent Text Reader

Abstract

The problem addressed by the present invention is to provide a method for manufacturing a solid-state battery with which it is possible to improve the adhesiveness between a positive electrode layer and a solid electrolyte layer that comes into contact with the positive electrode layer. [Solution] This method for manufacturing a solid-state battery comprises a laminate formation step for forming a solid electrolyte layer-positive electrode layer laminate, and the laminate formation step is provided with: a transfer pressing step for transferring and pressing a first solid electrolyte layer on a positive electrode active material layer in a positive electrode layer; a first pressurizing step for pressurizing the positive electrode layer to which the first solid electrolyte layer is transferred and the first solid electrolyte layer; and a second pressurization step, after the first pressurization step, in which a second solid electrolyte layer is disposed on the first solid electrolyte layer and pressurization is performed. The pressing pressure in the transfer pressing step is smaller than the pressing pressure in the first pressing step, and the content of the binder contained in the first solid electrolyte layer is equal to or greater than the content of the binder contained in the second solid electrolyte layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a solid battery. Background Art

[0002] In recent years, research and development related to secondary batteries that contribute to energy efficiency have been conducted in order to ensure that more people have access to sustainable and advanced energy that is affordable, reliable, and reliable.

[0003] As such secondary batteries, solid batteries such as lithium metal batteries and lithium ion secondary batteries are known, in which a solid electrolyte layer is disposed between a positive electrode layer and a negative electrode layer.

[0004] As a technology related to solid-state batteries, there is known a technology involving the following all-solid-state battery, wherein the all-solid-state battery has a first solid electrolyte layer adjacent to the negative electrode and a second solid electrolyte layer located between the first solid electrolyte layer and the positive electrode, and the Young's modulus of the first solid electrolyte layer is smaller than that of the second solid electrolyte layer (for example, refer to Patent Document 1).

[0005] [Prior Art Literature]

[0006] (Patent Document)

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2022-108202 Summary of the Invention

[0008] [Problems to be solved by the invention]

[0009] The subject of the technology disclosed in Patent Document 1 is to suppress the deterioration of the interface contact between the solid electrolyte layer and the positive and negative electrode layers, and to suppress the voltage drop during self-discharge. On the other hand, as a means of increasing the capacity of the solid battery, it can be considered to make the positive electrode active material layer as thick as possible. The thick positive electrode active material layer is preferably densified by pressing, in which case the positive electrode active material layer is easy to extend. Therefore, the solid electrolyte layer that abuts the positive electrode active material layer is preferably configured to follow the extension of the positive electrode active material layer during pressing, thereby improving the bonding property with the positive electrode active material layer.

[0010] The present invention has been made in view of the above, and an object of the present invention is to provide a method for manufacturing a solid battery that can improve the bonding between a solid electrolyte layer in contact with a positive electrode layer and the positive electrode layer.

[0011] [Technical means to solve the problem]

[0012] (1) A method for manufacturing a solid battery, comprising: a stacking step of stacking a positive electrode layer comprising a positive electrode collector layer and a positive electrode active material layer, and a solid electrolyte layer on the positive electrode active material layer to form a solid electrolyte layer-positive electrode layer stack; the stacking step comprises: a transfer pressing step of transferring a first solid electrolyte layer onto the positive electrode active material layer in the positive electrode layer and pressing the stacking step; a first pressurizing step of pressurizing the positive electrode layer to which the first solid electrolyte layer is transferred and the first solid electrolyte layer; and a second pressurizing step of arranging a second solid electrolyte layer on the first solid electrolyte layer and pressurizing the stacking step after the first pressurizing step; the pressing pressure in the transfer pressing step is smaller than the pressing pressure in the first pressurizing step, and the content of the binder contained in the first solid electrolyte layer is greater than the content of the binder contained in the second solid electrolyte layer.

[0013] According to the invention of (1), a method for manufacturing a solid battery can be provided, which can improve the bonding property between the solid electrolyte layer in contact with the positive electrode layer and the positive electrode layer.

[0014] (2) The method for manufacturing a solid battery according to (1), wherein the pressing pressure in the transfer pressing step is smaller than the pressing pressure in the second pressurizing step.

[0015] According to the invention of (2), even in the second pressurizing step, the solid electrolyte layer in contact with the positive electrode layer can easily follow the positive electrode layer and extend, thereby improving the bonding property with the positive electrode layer.

[0016] (3) The method for manufacturing a solid battery according to (1) or (2), wherein the thickness of the first solid electrolyte layer is thinner than the thickness of the second solid electrolyte layer.

[0017] According to the invention of (3), the solid electrolyte layer in contact with the positive electrode layer can also easily follow the extension of the positive electrode layer, and thus the bonding property with the positive electrode layer can be improved.

[0018] (4) The method for producing a solid battery according to any one of (1) to (3), wherein the content of the binder in the first solid electrolyte layer is 5% by volume or more and 25% by volume or less.

[0019] According to the invention of (4), the solid electrolyte layer in contact with the positive electrode layer can also easily follow the extension of the positive electrode layer, and thus the bonding property with the positive electrode layer can be improved.

[0020] (5) The method for producing a solid battery according to any one of (1) to (4), wherein the first solid electrolyte layer contains a fluorine-based binder.

[0021] According to the invention of (5), high-pressure pressing and thinning of the first solid electrolyte layer can be easily performed.

[0022] (6) The method for manufacturing a solid battery according to any one of (1) to (5) or 2, wherein the thickness of the first solid electrolyte layer is 3 μm or more and 15 μm or less.

[0023] According to the invention of (6), a solid battery can be obtained in which the first solid electrolyte layer is preferably thinned.

[0024] (7) The method for producing a solid battery according to any one of (1) to (6), wherein the pressing pressure in the transfer pressing step is 100 MPa.

[0025] According to the invention of (7), even in the first pressurizing step, the solid electrolyte layer in contact with the positive electrode layer can easily follow the positive electrode layer and extend, thereby improving the bonding property with the positive electrode layer.

[0026] (8) The method for producing a solid battery according to any one of (1) to (7), wherein the pressing pressure in the second pressurizing step is 150 MPa.

[0027] According to the invention of (8), the second solid electrolyte layer is moderately pressurized without being excessively pressurized, and thus the bonding between the second solid electrolyte layer and the third solid electrolyte layer can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a conceptual cross-sectional view showing the structure of a solid state battery according to an embodiment of the present invention.

[0029] Figure 2A A diagram illustrating a portion of the steps in a method for manufacturing a solid state battery according to an embodiment of the present invention.

[0030] Figure 2B A diagram illustrating a portion of the steps in a method for manufacturing a solid state battery according to an embodiment of the present invention. DETAILED DESCRIPTION

[0031] [Solid-state battery]

[0032] The solid battery 1 manufactured by the manufacturing method of the present invention is as follows Figure 1 As shown in FIG, there is an electrode stack body in which a negative electrode layer 2, a solid electrolyte layer 4 and a positive electrode layer 3 are stacked in this order. Figure 1 The structure in which the negative electrode layer 2, the solid electrolyte layer 4, the positive electrode layer 3, the solid electrolyte layer 4, and the negative electrode layer 2 are stacked in this order is described as a stacked structure of the solid battery 1. However, the structure of the solid battery 1 is not limited to the above. Figure 1In addition to the electrode stack shown, the solid battery may have a structure such as an outer casing that can be used in the solid battery.

[0033] The solid electrolyte layer 4 in the solid battery 1 includes at least a first solid electrolyte layer 43 disposed on the positive electrode layer 3 side and a second solid electrolyte layer 42 disposed adjacent to the first solid electrolyte layer 43. The solid electrolyte layer 4 may also include a third solid electrolyte layer 41 disposed on the negative electrode layer 2 side. In this embodiment, the solid electrolyte layer 4 is described as being composed of the above three layers. An intermediate layer 5 may also be optionally disposed between the negative electrode layer 2 and the solid electrolyte layer 4.

[0034] The solid battery 1 is not particularly limited and may be a lithium ion solid secondary battery or a lithium metal secondary battery.

[0035] (Negative electrode layer)

[0036] The negative electrode layer 2 includes a negative electrode active material layer 21 and a negative electrode current collector layer 22. The negative electrode active material layer 21 is not particularly limited and can be composed of a material that can be used as a negative electrode active material for a solid battery. Examples of negative electrode active materials constituting the negative electrode active material layer 21 include lithium metal, lithium alloys, silicon-based active materials such as Si and Si alloys, lithium titanate (Li4Ti5O 12 ) and other lithium transition metal oxides, TiO2, Nb2O3 and WO3 and other transition metal oxides, metal sulfides, metal nitrides, graphite, soft carbon and hard carbon and other carbon materials, metal indium, etc.

[0037] In addition to the above, the negative electrode active material layer 21 may also contain materials that can be contained in the negative electrode active material layer of a solid battery. Examples of the above materials include solid electrolytes, conductive additives, adhesives, and the like. As solid electrolytes, the same substances as those contained in the solid electrolyte layer 4 described later may be listed. As conductive additives, carbon black, natural graphite, carbon fibers, carbon nanotubes, and the like may be listed. As adhesives, nitrile polymers, polyester polymers, acrylic polymers, cellulose polymers, styrene polymers, styrene-butadiene polymers, vinyl acetate polymers, urethane polymers, fluoroethylene polymers, and the like may be listed.

[0038] The negative electrode current collector layer 22 is not particularly limited and can be made of copper, nickel, stainless steel, or the like. Examples of the shape of the negative electrode current collector layer 22 include foil, plate, mesh, nonwoven fabric, and foam. A portion of the negative electrode current collector layer 22 extends in a predetermined direction to form a negative electrode current collector tab 22a.

[0039] (Solid electrolyte layer)

[0040] The solid electrolyte layer 4 is formed between the negative electrode layer 2 and the positive electrode layer 3. In this embodiment, the solid electrolyte layer 4 has a structure in which a first solid electrolyte layer 43, a second solid electrolyte layer 42, and a third solid electrolyte layer 41 arranged on the negative electrode layer side are stacked in this order.

[0041] The first solid electrolyte layer 43 is arranged in contact with the positive electrode active material layer 31 in the positive electrode layer 3. There is no particular limitation on the solid electrolyte constituting the first solid electrolyte layer 43, as long as it is a material that can be used as an electrolyte for a solid battery. For example, sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes, inorganic solid electrolytes such as lithium salts, or polymer-based solid electrolytes such as polyethylene oxide can be cited. The above-mentioned solid electrolytes can be used alone or in combination of two or more.

[0042] The first solid electrolyte layer 43 includes a binder in addition to the solid electrolyte material. As the binder, the same substance as the binder that can be included in the negative electrode active material layer 21 can be used. The content of the binder in the first solid electrolyte layer 43 relative to the total mass of the first solid electrolyte layer 43 is greater than the content of the binder in the second solid electrolyte layer 42 relative to the total mass of the second solid electrolyte layer 42. The upper limit of the content of the above-mentioned binder in the first solid electrolyte layer 43 is, for example, 25% by mass. The content of the above-mentioned binder in the first solid electrolyte layer 43 is preferably 10 to 30% by mass. As a result, when the positive electrode layer 3 is pressed, the first solid electrolyte layer 43 easily extends along with the positive electrode layer 3. In addition, the pressing pressure in the transfer pressing process described later can be reduced.

[0043] The first solid electrolyte layer 43 preferably contains a fluorine-based polymer (fluorine-based binder). Examples of fluorine-based binders include polyvinylidene difluoride (PVdF). This facilitates high-pressure pressing and thinning of the solid electrolyte layer.

[0044] The first solid electrolyte layer 43 may contain, in addition to the solid electrolyte material and the binder, materials that can be used in the solid electrolyte layer of a solid battery.

[0045] The thickness of first solid electrolyte layer 43 (the length of each layer in the stacking direction) is preferably thinner than the thickness of second solid electrolyte layer 42. The thickness of first solid electrolyte layer 43 is preferably 3 to 15 μm, for example.

[0046] The second solid electrolyte layer 42 is arranged adjacent to the first solid electrolyte layer 43. There is no particular limitation on the solid electrolyte material constituting the second solid electrolyte layer 42, and the same material as the solid electrolyte material constituting the first solid electrolyte layer 43 can be used. Like the first solid electrolyte layer 43, the second solid electrolyte layer 42 may also contain a binder and the like in addition to the solid electrolyte material. The content of the binder in the second solid electrolyte layer 42 is less than the content of the binder in the first solid electrolyte layer 43. The content of the binder in the second solid electrolyte layer 42 is preferably 10 to 30% by mass. This can improve the energy density of the solid battery 1. The second solid electrolyte layer 42 may also include a support. The support may be a three-dimensional structure such as a mesh, a woven fabric, a non-woven fabric, an embossed body, a punched body, an expanded body, or a foamed body. The second solid electrolyte layer 42 may not include the support.

[0047] The thickness of second solid electrolyte layer 42 (the length of each layer in the stacking direction) is preferably greater than the thickness of first solid electrolyte layer 43. The thickness of second solid electrolyte layer 42 is preferably 10 to 50 μm, for example.

[0048] The third solid electrolyte layer 41 is a layer that is arbitrarily arranged and is arranged on the negative electrode layer side. The third solid electrolyte layer 41 can also be arranged adjacent to the negative electrode layer 2. Figure 1 As shown, when the solid battery 1 includes the intermediate layer 5 , the third solid electrolyte layer 41 may be arranged adjacent to the intermediate layer 5 .

[0049] The solid electrolyte material constituting the third solid electrolyte layer 41 is not particularly limited, and the same material as the solid electrolyte material constituting the first solid electrolyte layer 43 can be used. Like the first solid electrolyte layer 43, the third solid electrolyte layer 41 may also contain a binder or the like in addition to the solid electrolyte material. The binder content in the third solid electrolyte layer 41 is preferably 1 to 20% by mass relative to the total mass of the first solid electrolyte layer 43. This can increase the energy density of the solid battery 1.

[0050] (positive electrode layer)

[0051] The positive electrode layer 3 includes a positive electrode active material layer 31 and a positive electrode current collector layer 32. In this embodiment, the positive electrode layer 3 has a structure in which two positive electrode active material layers 31 are stacked on both sides of a single positive electrode current collector layer 32. However, the structure of the positive electrode layer 3 is not limited to the above structure, and a structure in which one positive electrode active material layer 31 is stacked on a single side of a single positive electrode current collector layer 32 may also be used.

[0052] The positive electrode active material layer 31 is not particularly limited and can be composed of a material that can be used as a positive electrode active material for a solid battery. Examples of the positive electrode active material constituting the positive electrode active material layer 31 include LiCoO2, LiNiO2, LiCo x Ni y Mn z O2 (x+y+z=1), LiVO2, LiCrO2 and other layered positive electrode active material particles; LiMn2O4, Li(Ni 0.25 Mn 0.75 )2O4, LiCoMnO4, Li2NiMn3O8 and other spinel positive electrode active materials; LiCoPO4, LiMnPO4, LiFePO4 and other olivine positive electrode active materials; solid solution oxides (Li2MnO3-LiMO2 (M is Co, Ni, etc.)), polyaniline, polypyrrole and other conductive polymers; sulfides such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds; mixtures of sulfur and carbon; etc. The above-mentioned positive electrode active materials may use one of the above-mentioned materials or a structure composed of two or more of the above-mentioned materials.

[0053] The thickness of the positive electrode active material layer 31 (the length of each layer in the stacking direction) is preferably 3 to 15 μm, for example. This can increase the battery capacity of the solid battery 1 .

[0054] An insulating frame 6 may also be provided on the periphery of the positive electrode active material layer 31. The insulating frame 6 can prevent short circuits in the solid battery 1 and improve strength. In the present embodiment, the insulating frame 6 is configured to cover the side surfaces of the two positive electrode active material layers 31 formed on both sides of the positive electrode collector layer 32. In addition, the insulating frame 6 abuts against a portion of the stacking surface of the positive electrode collector layer 32 and has a gap for the positive electrode collector tab 32a described later to extend. There is no particular limitation on the material constituting the insulating frame 6, and examples thereof include insulating oxides such as alumina, resins such as polyvinylidene fluoride (PVDF), and rubbers such as styrene-butadiene rubber (SBR).

[0055] The positive electrode current collector layer 32 is not particularly limited and can be made of, for example, aluminum, stainless steel, conductive carbon (graphite, carbon nanotubes, etc.). Examples of the shape of the positive electrode current collector layer 32 include foil, plate, mesh, non-woven fabric, and foam. A portion of the positive electrode current collector layer 32 extends in a predetermined direction to form a positive electrode current collector tab 32a.

[0056] (Middle layer)

[0057] The intermediate layer 5 is disposed between the negative electrode layer 2 and the solid electrolyte layer 4. For example, if the solid battery 1 is a lithium metal battery, the intermediate layer 5 has the function of uniformly depositing lithium metal. Thus, the interface between the intermediate layer 5 and the solid electrolyte layer 4 is stabilized. If the solid battery 1 is a lithium metal secondary battery having the intermediate layer 5, the solid battery 1 may also be an anode-less battery in which the negative electrode active material layer 21 is not present during the initial charge. In this case, a lithium metal layer is formed as the negative electrode active material layer 21 after the initial charge and discharge.

[0058] The material constituting the intermediate layer 5 is not particularly limited, and examples thereof include metals or amorphous carbon that can be alloyed with lithium. Examples of metals that can be alloyed with lithium include tin (Sn), silicon (Si), zinc (Zn), magnesium (Mg), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), and antimony (Sb). Metals that can be alloyed with lithium may also be nanoparticles. Examples of amorphous carbon include carbon blacks such as acetylene black, furnace black, and Ketjen black, coke, and activated carbon. Amorphous carbon may be either easily graphitized carbon (soft carbon) or difficultly graphitized carbon (hard carbon), CNTs (carbon nanotubes), fullerenes, or graphene. In addition to the above-mentioned substances, the intermediate layer may also include a binder.

[0059] [Method for manufacturing solid-state batteries]

[0060] Below, use Figure 2A 、 Figure 2B The solid-state battery manufacturing method of this embodiment is described. This method is a method for manufacturing a solid-state battery having an electrode stack La, which is sequentially stacked with a negative electrode layer, an intermediate layer, a solid electrolyte layer, and a positive electrode layer. The solid-state battery manufacturing method of this embodiment includes a stack formation step in which the solid electrolyte layer 4 is stacked on the positive electrode active material layer 31 in the positive electrode layer 3 to form a solid electrolyte layer-positive electrode layer stack.

[0061] The laminate forming step includes a transfer pressing step, a first pressing step, and a second pressing step in this order.

[0062] Transfer pressing process such as Figure 2A As shown, the first solid electrolyte layer 43 is transferred onto the positive electrode active material layer 31 in the positive electrode layer 3 and then pressed. A specific example of a method for performing the transfer and pressing step is a method using a solid electrolyte layer transfer sheet. The solid electrolyte layer transfer sheet can be obtained, for example, by applying a slurry containing a material constituting the first solid electrolyte layer 43 dispersed in a solvent onto a support sheet and drying the slurry.

[0063] In the transfer pressing step, the first solid electrolyte layer 43 is transferred onto the positive electrode active material layer 31 in the positive electrode layer 3 and pressed. A pressure of 50 to 500 MPa can be used at room temperature (e.g., 10 to 35°C). The pressing pressure in the transfer pressing step is lower than the pressing pressure in the first pressing step. The pressing pressure in the transfer pressing step is preferably 100 MPa. Furthermore, it is preferably lower than the pressing pressure in the second pressing step. Because the first solid electrolyte layer 43 contains a relatively high amount of binder, the pressing pressure in the transfer pressing step can be reduced. Furthermore, by setting the pressing pressure in the transfer pressing step as low as possible, the amount of extension of the first solid electrolyte layer 43 during the transfer pressing step can be reduced. This leaves room for the first solid electrolyte layer 43 to extend in the subsequent first pressing step, allowing the first solid electrolyte layer 43 to extend in line with the positive electrode layer 3. This improves the bonding between the first solid electrolyte layer 43 and the positive electrode active material layer 31.

[0064] The first press step applies pressure to the laminate L1 (the positive electrode layer 3 - the first solid electrolyte layer 43 laminate) obtained in the transfer press step. This first press step densifies (increases the density) the positive electrode active material layer 31 within the positive electrode layer 3. The pressing conditions in the first press step can be, for example, a temperature of 25-100°C and a pressure of 800-1200 MPa.

[0065] The second pressurization process is as follows Figure 2B The figure shows a process in which, after the first pressurization step, the second solid electrolyte layer 42 is placed on the first solid electrolyte layer 43 of the stack L1 (the stack of the positive electrode layer 3 and the first solid electrolyte layer 43) and pressurized to obtain the solid electrolyte layer-positive electrode layer stack La. The pressing conditions in the second pressurization step can be, for example, 50 to 500 MPa at room temperature (e.g., 10 to 35°C). The preferred pressing condition in the second pressurization step is 150 MPa.

[0066] The method for manufacturing a solid battery of this embodiment may also include steps other than those described above. For example, it may also include steps for obtaining Figure 1 The process of forming the solid-state battery 1 shown in FIG. For example, the process may include: transferring the intermediate layer 5 onto the negative electrode layer 2 to obtain a negative electrode layer-intermediate layer laminate; placing the third solid electrolyte layer 41 on the intermediate layer of the negative electrode layer-intermediate layer laminate and pressing the laminate to obtain a negative electrode layer-intermediate layer-solid electrolyte layer laminate; placing two negative electrode layer-intermediate layer-solid electrolyte layer laminates with the solid electrolyte layers facing each other, placing the solid electrolyte layer-positive electrode layer laminate La between the facing solid electrolyte layers, and pressing the laminate as a whole; and the like.

[0067] In each of the above steps, the press bonding apparatus is not particularly limited, and a roller press, a flatbed press, or a hydrostatic press (CIP, WIP) apparatus may be used. When a roller press is used for press bonding, the objects to be press bonded may be conveyed in the same direction or in different directions on the roller press.

[0068] While preferred embodiments of the present invention have been described above, the present invention is not limited to the aforementioned embodiments and can be modified as desired without impairing the effects of the present invention. For example, the method for manufacturing a solid battery of the present invention can also include any additional steps in addition to those described above.

[0069] Reference numerals

[0070] 1Solid-state battery

[0071] 2 negative electrode layer

[0072] 3 positive electrode layer

[0073] 31 positive electrode active material layer

[0074] 32 positive electrode collector layer

[0075] 4 Solid electrolyte layer

[0076] 42 Second solid electrolyte layer

[0077] 43 First solid electrolyte layer

Claims

1. A method for manufacturing a solid battery, comprising: a stacking step of stacking a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer, and a solid electrolyte layer on the positive electrode active material layer to form a solid electrolyte layer-positive electrode layer stack; The aforementioned laminate forming step comprises: a transfer and pressing step of transferring the first solid electrolyte layer onto the positive electrode active material layer in the positive electrode layer and pressing the layer; a first pressurizing step of pressurizing the positive electrode layer to which the first solid electrolyte layer is transferred and the first solid electrolyte layer; and a second pressurizing step of placing a second solid electrolyte layer on the first solid electrolyte layer and pressurizing the layer after the first pressurizing step; The pressing pressure in the transfer pressing step is smaller than the pressing pressure in the first pressing step. The content of the binder contained in the first solid electrolyte layer is equal to or greater than the content of the binder contained in the second solid electrolyte layer.

2. The method for manufacturing a solid battery according to claim 1, wherein: The pressing pressure in the transfer pressing step is smaller than the pressing pressure in the second pressing step.

3. The method for manufacturing a solid battery according to claim 1 or 2, wherein: The thickness of the first solid electrolyte layer is thinner than the thickness of the second solid electrolyte layer.

4. The method for manufacturing a solid battery according to claim 1 or 2, wherein: The content of the binder in the first solid electrolyte layer is 5% by volume or more and 25% by volume or less.

5. The method for manufacturing a solid battery according to claim 1 or 2, wherein: The first solid electrolyte layer contains a fluorine-based binder.

6. The method for manufacturing a solid battery according to claim 1 or 2, wherein: The thickness of the first solid electrolyte layer is 3 μm or more and 15 μm or less.

7. The method for manufacturing a solid battery according to claim 1 or 2, wherein: The pressing pressure in the transfer pressing step was 100 MPa.

8. The method for manufacturing a solid battery according to claim 1 or 2, wherein: The pressing pressure in the second pressing step is 150 MPa.

Citation Information

Patent Citations

  • All-solid-state battery

    JP2022108202A